Aquatic protected area system in the Qinghai–Tibet Plateau: establishment, challenges and prospects - Li, Haoran; Tan, Lu; Li, Xianfu; Cai, Qinghua (Frontiers in Ecology and Evolution, 2024)
Conservation of wetlands on the Qinghai–Tibet Plateau is vital to the ecological security of China and even all of Asia. In this study, we investigated the aquatic protected area system established by the Chinese government in the Qinghai–Tibet Plateau. In general, 9 categories of aquatic protected areas have been established in this area, linked to the International Union for Conservation of Nature classification system of protected areas. The diverse main protection objectives of different protected areas have played a key role in wetland conservation. However, the protection of wetland environments and aquatic organisms has been insufficient in some atypical protected areas and local protected areas. We further constructed a list of important aquatic organisms in the Qinghai–Tibet Plateau and analyzed the protected status of those important species through gap analysis. A total of 156 important aquatic species were identified, with 8 gap species and 18 inadequately protected species. It is encouraging that none of the national key protected species are gap species, but there are 4 gap species that are threatened species on “China’s red list”. In addition, we found that 17 important species are designated as Data Deficient or Not Evaluated on “China’s red list”, including 8 national key protected species. Finally, we propose the prospects for solving the existing problems of aquatic protected area systems: integrating aquatic protected areas, enhancing the status of community-based conservation, and increasing investment in important aquatic organism research.